2016
DOI: 10.4028/www.scientific.net/kem.718.143
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Pottery Stone as a Replacing Material for Vitreous Ceramic Sanitary Ware Production: A Case Study in Khon Kaen, Thailand

Abstract: The aim of this work was to determine the properties of vitreous ceramic sanitary ware bodies according to the production of Khon Kaen ceramic sanitary ware industry, Thailand. Pottery stone was used as a replacing material in the commercial ceramic sanitary ware body formulation. The cast slurry of seven formulations was prepared by wet milling. The rheological properties (density and torsion viscosity) were investigated before slip casting. The test pieces were fired at 1175, 1200 and 1225๐C and the physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…6 On the other hand, toseki has been exploited in Japan since at least the 17th century and its industrial application peaked in the 1970s, as also observed for another type of flux: the sericitic roseki. 7,8 Sericite-bearing pottery stone has been also utilized in Korea, 9 Russia, 10 Kazakhstan, 11 Thailand, 12 and Indonesia. 13 Eurite, a pervasively sericitized aplite, 14 has been widely used in the ceramic tile industry since the 1970s.…”
Section: Introductionmentioning
confidence: 99%
“…6 On the other hand, toseki has been exploited in Japan since at least the 17th century and its industrial application peaked in the 1970s, as also observed for another type of flux: the sericitic roseki. 7,8 Sericite-bearing pottery stone has been also utilized in Korea, 9 Russia, 10 Kazakhstan, 11 Thailand, 12 and Indonesia. 13 Eurite, a pervasively sericitized aplite, 14 has been widely used in the ceramic tile industry since the 1970s.…”
Section: Introductionmentioning
confidence: 99%